Salt loading as a promising approach to study the dopaminergic phenotype of neurons of the supraoptic nucleus in mice - Alyona E. Bannikova; Tatiana S. Pronina; Dmitry V. Troshev; Vsevolod V. Bogdanov; Anna A. Kolacheva; Ekaterina N. Pavlova; Victor E. Blokhin; Varvara I. Kalashnikova; Michael V. Ugrumov (PLoS ONE, 2026)
Until the beginning of this century, neurons of the supraoptic nucleus (SON) were repeatedly shown to express tyrosine hydroxylase (TH) in salt loaded rats. However, its role remains unsolved due to methodological problems. Given that these issues can now be solved using transgenic mice and more advanced methods, the aim of this study was to reproduce the salt loading models used in rats, in C57BL/6 mice and transgenic mice expressing the green fluorescent protein gene under the TH promoter. Our study also attempted to identify a model that would most significantly increase TH synthesis in vasopressinergic neurons. This was assessed with immunocytochemistry by measuring the number of TH-immunoreactive neurons in the SON and the intraneuronal content of TH-immunoreactive material in individual neurons. In the first model, when using 3% NaCl as drinking water, the highest number of TH-immnopositive neurons was detected on the 3rd day, while the intraneuronal TH content did not change. In the second model, 10 hours after the intraperitoneal administration of 8.5% NaCl (experiment) or 0.9% NaCl (control), the number of TH-immunopositive neurons was significantly higher than in the first model. Moreover, the intraneuronal content of TH increased. Additional PCR analysis showed in the second model an increase in the expression of the TH gene and genes of some transcription factors (Sp1, Atf4, c-Fos, c-Jun) that initiate the TH gene expression in SON. Thus, we developed and characterized a salt loading model in mice with the highest level of TH synthesis, which will be used in the future to assess the functional significance of this protein.